Horas Tondi Madingin Pir Tondi Matogu Pernikahan Baginda Harahap Dengan Fitri Dalimunthe - Baginda Harahap; Fitri Dalimunthe (Cebong Journal, 2022)
Marriage is something that everyone wants, and is the most beautiful moment in life which is the sunnah of the apostle for Muslims. Marriage is a very great gift from God and its meaning is very deep, so this marriage is one of the benchmarks for him to become an adult or not. His Baginda Harahap is the son of Arpin Harahap who was born in the village of Siboruangin in 1991, Fitri Dalimunthe the daughter of Sutan Syahrir Dalimunthe who was born in the village of Tanjung Baringin 1992. These two couples are very different regions, clans, traits and of course education. However, in this marriage it will be proven whether this difference will be a problem in the family later or will be peace and happiness. While Allah and His Messenger say that goodness, serenity, sufficiency, weakness, strength will be obtained from a partner.